Climate Change Impacts for the Conterminous USA An Integrated Assessment - Rosenberg, Norman J.; Edmonds, James A. (Springer Netherlands : Imprint: Springer, 2005)
In this volume, an improved Integrated Assessment methodology is used to analyse climate change impacts on agriculture, water resources, unmanaged ecosystems, irrigation, and land use in the United States and the economic implications of these impacts. This book contains a series of papers documenting the methods, models, analysis and results of this integrated assessment for a wide ranging set of scenarios describing future climate change. Innovations described include the integration of water resource and agricultural modeling and the refinement of an agriculture and land-use economics model to incorporate results from process-level ecosystem models of agriculture, water and natural ecosystem resources. Scenarios selected for this study address a range of uncertainties associated with choice of climate model, presence or absence of a 'CO2-fertilization effect', impacts on international trade in agricultural commodities and their consequences for producers and consumers. This book will be useful to natural and social scientists who use integrated assessment methods. The analyses and conclusions will be of particular interest to policy makers needing to know what the specific impacts of climatic change could be and to those charged with developing strategies for mitigation and adaptation to climate change and climate variability. Reprinted from Climatic Change Vol. 69, No. 1, 2005.